Designing an Elastic-Logistics-Oriented Fleet Management System for Petralog Using a Design Thinking Approach - Fajar Irvan Setyawan; Astri Ghina (Asian Journal of Management Analytics, 2026)
The logistics sector in Indonesia contributes significantly to national GDP yet suffers from structural inefficiencies including low truck utilisation, manual fleet management, and fluctuating operational demand. Petralog, a regional logistics provider, faces similar issues, especially in coordinating internal and external fleets under elastic logistics practices. This study develops a high-fidelity Fleet Management System (FMS) prototype using the Design Thinking framework to address operational pain points and enhance efficiency. Qualitative insights were collected from six stakeholders, followed by prototype evaluation using the UEQ-S and Microsoft Clarity analytics. Results indicate high user acceptance, with a performance score of 84/100 and no rage clicks detected. UEQ-S benchmarking places the prototype within the “Excellent” category (top 10%), reflecting strong pragmatic quality (2.50) and hedonic quality (1.90).